Zoonotic foodborne diseases in a tertiary healthcare setting: diagnostics, resistance and underreporting of campylobacteriosis in Northern Portugal. (March 2022) - Rocha, R.; Matos, M.I.; Pinto, J.; Sarmento, A.
Abstract : Purpose: Campylobacteriosis and salmonellosis are the two most common zoonotic foodborne diseases. In Europe, although incidence rates seem to be stable in the last five years, growing antimicrobial resistance is concerning. In Portugal, although reporting of these diseases is mandatory, it is estimated that a significant percentage of cases diagnosed in tertiary health care is not reported. The aim of this study is to describe the nature of Campylobacter isolated in our hospital, focusing on resistance trends, and to determine rates of underreporting. Methods & Materials: We reviewed the Campylobacter sp. identified at the microbiology laboratory of the São João University Hospital by isolation in culture or PCR amplification, from patients presenting with symptoms at the emergency department or out-patient setting. The study was conducted between 2015 and 2020. Results: Between 2015 and 2020, 398 Campylobacter sp. isolates were identified. Most patients were male (61.8%). The median age was 7 (50% under 10 years). 88.2% of isolations were from fecal samples and 4.5% from blood, mostly by culture (only 6.5% by PCR). Most products were collected in the pediatrics emergency (55.3%), pediatrics ward (16.8%) and adult ward (10.6%). The most commonly identified species was C. jejuni (81.7%), followed by C. coli (16.2%) and C. fetus (1.8%). Of the 184 isolates with available antimicrobial susceptibility testing, 94.6% were resistant to ciprofloxacin, 71.2% to tetracycline and 13.8% to erythromycin. Resistance to erythromycin was significantly higher in C. coli (63.3% vs 4.1%). Resistance profiles and species isolated were not significantly different between the years of this study. Only 31% of cases were notified to the National Monitoring System between 2016 and 2019. Conclusion: Our study underlines the burden of campylobacteriosis in children under 5 years old. C. jejuni was the most frequent species identified, as expected by the results of similar studies. A significant (but stable) resistance to fluoroquinolones was observed in our setting. Resistance to macrolides is considerable and concerning, especially in C. coli . Underreporting, even in hospital settings, may deter efforts to control the emergence of these pathogens and their increasing resistance to first line antibiotics.